Conscientious objection to abortion: how to strike a legal and ethical balance between conflicting rights? - Negro, Francesca; Varone, Maria Cristina; Del Rio, Alessandro; Marinelli, Susanna; Basile, Giuseppe (Acta Biomedica Atenei Parmensis, 2022)
The Italian Supreme Court ruling no. 18901 of May 13, 2021 has determined that doctors who are opposed to abortion can refuse to perform it on grounds of conscience, but such a refusal does not exempt them from providing assistance to the woman before and after the procedure itself. The legalization of abortion should be considered within a broader strategy to put an end to underground and unsafe abortions, to raise awareness and enhance reproductive education and accessibility to contraceptive methods. The authors have set out to briefly analyze the legal and ethical complexities inherent in the effort to reconcile women’s reproductive autonomy and freedom of choice with conscience-based refusal on the part of numerous healthcare professionals. Such an apparent conflict highlights the need for an ethically tenable solution that takes into account the dignity of unborn children, based on the conviction of many healthcare professionals primarily based on moral and religious tenets, that life begins at conception as well as the reproductive freedom and autonomy of women.